The Streptomyces NrdR Transcriptional Regulator Is a Zn Ribbon/ATP Cone Protein That Binds to the Promoter Regions of Class Ia and Class II Ribonucleotide Reductase Operons - Grinberg, Inna (American Society for Microbiology, 2006)
Ribonucleotide reductases (RNRs) catalyze the conversion of ribonucleotides to deoxyribonucleotides and are essential for de novo DNA synthesis and repair. Streptomyces spp. contain genes coding for two RNRs, either of which is sufficient for vegetative growth. The class Ia RNR is encoded by the nrdAB genes, and the class II RNR is encoded by nrdJ, which is coexpressed with nrdR. We previously showed that the Streptomyces coelicolor nrdR gene encodes a protein, NrdR, which represses transcription of both sets of RNR genes. NrdR is a member of a highly conserved family of proteins that is confined exclusively to prokaryotes. In this report, we describe a physical and biochemical characterization of the S. coelicolor NrdR protein and show that it is a zinc-ATP/dATP-containing protein that binds to the promoter regions of both Streptomyces RNR operons. The NrdR N terminus contains a zinc ribbon motif that is necessary for binding to the upstream regulatory region of both RNR operons. The latter contains two 16-bp direct repeat sequences, termed NrdR boxes, which are located proximal to, or overlap with, the promoter regions. These experiments support the view that NrdR controls the transcription of RNR genes by binding to the NrdR box sequences. We also show that the central NrdR ATP cone domain binds ATP and dATP and that mutations that abolish ATP/dATP binding significantly reduce DNA binding, suggesting that the ATP cone domain may allosterically regulate NrdR binding. We conclude that NrdR is a widely conserved regulator of RNR genes, binding to specific sequence elements in the promoter region and thereby modulating transcription.